2013
DOI: 10.1108/sampj-10-2011-0030
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effects of the adoption of an environmental information system on top management's commitment and environmental performance

Abstract: PurposeThis paper aims to examine the antecedent factor, top management's commitment to environmental sustainability, for the adoption of a sophisticated internal environmental information system; measured by the broad‐scope, timeliness, aggregation and integration of such information. The paper also seeks to examine whether the availability of such a system would lead to improved environmental performance.Design/methodology/approachThe paper investigates responses from a survey of Chief Financial Officers or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 82 publications
4
50
0
7
Order By: Relevance
“…Top management committee by understanding the importance of environmental initiatives (in terms of increased performance), decides for environmental sustainability; they will be considered as committed. Many researchers found that there is a significant or positive relationship within the commitment of toplevel management and environmental performance (Spencer, Adams, & Yapa, 2013). EP has been an effective tool because of bigger cost on environmental operation; regulatory of markets as well as public pressure; due to this increased importance day-byday, the government requires its reports from companies so top-level management commitment can highlight the issues and implement EMA systems to get information about issues, therefore, its performance can be increased.…”
Section: Top Management Commitment Environmental Management Accountimentioning
confidence: 99%
See 2 more Smart Citations
“…Top management committee by understanding the importance of environmental initiatives (in terms of increased performance), decides for environmental sustainability; they will be considered as committed. Many researchers found that there is a significant or positive relationship within the commitment of toplevel management and environmental performance (Spencer, Adams, & Yapa, 2013). EP has been an effective tool because of bigger cost on environmental operation; regulatory of markets as well as public pressure; due to this increased importance day-byday, the government requires its reports from companies so top-level management commitment can highlight the issues and implement EMA systems to get information about issues, therefore, its performance can be increased.…”
Section: Top Management Commitment Environmental Management Accountimentioning
confidence: 99%
“…The third part consisted of the questions regarding the variables and the scale used for all the items was five-point Likert scale. To measure the environmental performance, 7 items were included in the questionnaire which was adapted from (Latan et al, 2018) and they adopted these items from (Lisi, 2015) and (Spencer et al, 2013). One sample item from those questions is "Firm is preparing annual environmental performance report" consisting of strongly disagree to strongly agree on a scale.…”
Section: Measurement and Scales Adaptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary stakeholder group includes social and political stakeholders that play a fundamental role in obtaining business credibility and acceptance of its activities (NGOs/activists, communities, governments and competitors). Several studies investigated the positive effects of engaging accountants in CSR, particularly in terms of the environmental dimension (Albelda, 2011;Yang-Spencer et al, 2013). Finally, Hart and Sharma (2004) add the existence of peripheral stakeholders or "fringe" stakeholders as those parties not visible or readily identifiable with the firm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The null 1190 To test the meditational hypothesis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19),this study used Judd and Kenny's (1981) a series of regression procedure, where this procedure adopted by many previous studies (Yousef 2000;Morris et al 2003;Carlson & O'Cass 2011;Spencer et al 2013). Testing for the mediation requires a series of three regression equatio]ls:…”
Section: Endorsement and Customer Based Brand Equitymentioning
confidence: 99%